2007
DOI: 10.1063/1.2817087
|View full text |Cite
|
Sign up to set email alerts
|

Efficient GeV ion generation by ultraintense circularly polarized laser pulse

Abstract: The interaction of an ultraintense circularly polarized laser pulse and a solid target is studied by one-dimensional particle-in-cell simulations. Ions at the front of the target are reflected by a moving quasisteady electrostatic field and obtain a relativistic velocity. At a laser intensity of 1022W∕cm2, almost half of the laser energy is transferred to ions and GeV ions are obtained. Effects of laser polarization state and target thickness on the laser energy conversion are investigated. It is found that a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
88
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(94 citation statements)
references
References 24 publications
5
88
1
Order By: Relevance
“…[11,12] are devoted to extending its range of operation towards lower electromagnetic wave intensities. The interaction of a high intensity laser pulse with extended plasmas in the RPDA (or 'Laser Piston') regime has been simulated in [13]. In Refs.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] are devoted to extending its range of operation towards lower electromagnetic wave intensities. The interaction of a high intensity laser pulse with extended plasmas in the RPDA (or 'Laser Piston') regime has been simulated in [13]. In Refs.…”
Section: Introductionmentioning
confidence: 99%
“…High-energy ions accelerated by such intense laser interacting with the solid target can be prospectively applied in fast ignition for inertial confinement fusion [3,4], medical therapy [5,6], and proton imaging [7], among others. Radiation pressure acceleration (RPA) using circularly polarized (CP) laser pulses provides a promising way to obtain a high-energy ion beam with monoenergetic spectrum in a much more efficient manner, compared with target normal sheath acceleration [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Yan et al [12] proposed the phase-stable-acceleration (PSA) mechanism in the RPA regime [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] to synchronously accelerate and bunch ions within skin depth of the laser pulse to get a monoenergetic ion beam in the longitudinal direction.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the absence of an oscillatory component in the ponderomotive force of a CP laser, electron heating is suppressed, so that a highly monoenergetic ion bunch can be obtained. 23,24 However, higher-dimensional simulations showed that the RPA scheme is susceptible to transverse Weibel-and Rayleigh-Taylor-like instabilities. [25][26][27] As a result, the final ion energy spectrum exhibits a sharp cutoff in the otherwise quasithermal profile.…”
Section: Introductionmentioning
confidence: 99%